Brain GLP-1 and insulin sensitivity. (15th December 2015) - Sandoval, Darleen; Sisley, Stephanie R.
Abstract: Type 2 diabetes is often treated with a class of drugs referred to as glucagon-like peptide-1 (GLP-1) analogs. GLP-1 is a peptide secreted by the gut that acts through only one known receptor, the GLP-1 receptor. The primary function of GLP-1 is thought to be lowering of postprandial glucose levels. Indeed, medications utilizing this system, including the long-acting GLP-1 analogs liraglutide and exenatide, are beneficial in reducing both blood sugars and body weight. GLP-1 analogs were long presumed to affect glucose control through their ability to increase insulin levels through peripheral action on beta cells. However, multiple lines of data point to the ability of GLP-1 to act within the brain to alter glucose regulation. In this review we will discuss the evidence for a central GLP-1 system and the effects of GLP-1 in the brain on regulating multiple facets of glucose homeostasis including glucose tolerance, insulin production, insulin sensitivity, hepatic glucose production, muscle glucose uptake, and connections of the central GLP-1 system to the gut. Although the evidence indicates that GLP-1 receptors in the brain are not necessary for physiologic control of glucose regulation, we discuss the research showing a strong effect of acute manipulation of the central GLP-1 system on glucose control and how it is relevant to type 2 diabetic patients. Highlights: Glucagon-like peptide-1 (GLP-1) can be produced by the brain and has receptors in key brain areas for glucose control. Central manipulations of the GLP-1 system can alter glucose homeostasis. Brain GLP-1 receptors are not needed for normal glucose control or to lower glucose by long-acting GLP-1 analogs in rodents.